THE GIZ-EN-SCENE GROUP: ACCOUNT OF AN EXPERIENCE IN DRAMATIZED READINGS OF CLASSICAL TEXTS - Toledo Prado, Joao Batista [UNESP] (Univ Estadual Paulista-unesp, 2017)
This text consists of an account of the experience gained over many years of presentations made by the Giz-en-Scene Group, which was founded in 1987 by professors of Classical Philology from UNESP (Latin, Greek) and USP (Sanskrit), during the second national meeting of the Brazilian Society for Classical Studies (SBEC) and which remains active until the present. Throughout its existence, the Giz-en-Scene Group has presented its performances of dramatized readings in conferences, schools, events and even public squares, taking texts of Classical Antiquity to wherever there was interest in receiving them. Its objective is to disseminate ancient texts, with didactic and cultural dissemination purposes. The performances staged by the Giz-en-Scene Group contain scenographic elements and always put a dramatic emphasis to text reading.
Keywords: Ancient theater; Dramatized readings; French semiotics; Giz-en-Scene Group; Text adaptation; Translation